1991
DOI: 10.1200/jco.1991.9.8.1357
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of salvage surgery to the management of childhood osteosarcoma.

Abstract: Between January 1970 and December 1988, 174 consecutive patients under the age of 20 years with curatively resected primary osteosarcoma were treated at our institute; 72 in the years of 1970 to 1981 and 102 in the years 1982 to 1988. In the latter period, adjuvant chemotherapy was replaced by neoadjuvant programs, and new criteria were adopted for the management of lung metastases, consisting in early bilateral surgical staging and lung resection through median sternotomy for all patients with purely intratho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 16 publications
3
34
0
2
Order By: Relevance
“…In many series, the number of patients treated with second-line chemotherapy was too small to draw conclusions regarding the impact on survival. 7,21 Pastorino et al 13 and Tabone et al 15 observed no difference in survival with or without second-line chemotherapy. However, chemotherapy was given selectively to patients with multiple pulmonary nodules or with an RFI shorter than 1 year RFI 13 or to patients with multiple recurrent tumors or tumors that were difficult to resect.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In many series, the number of patients treated with second-line chemotherapy was too small to draw conclusions regarding the impact on survival. 7,21 Pastorino et al 13 and Tabone et al 15 observed no difference in survival with or without second-line chemotherapy. However, chemotherapy was given selectively to patients with multiple pulmonary nodules or with an RFI shorter than 1 year RFI 13 or to patients with multiple recurrent tumors or tumors that were difficult to resect.…”
Section: Discussionmentioning
confidence: 96%
“…7,21 Pastorino et al 13 and Tabone et al 15 observed no difference in survival with or without second-line chemotherapy. However, chemotherapy was given selectively to patients with multiple pulmonary nodules or with an RFI shorter than 1 year RFI 13 or to patients with multiple recurrent tumors or tumors that were difficult to resect. 15 In contrast, Saeter et al 19 concluded that the delivery of "modern intensive chemotherapy" (p. 1090) improved overall survival when compared with patients treated with no or inadequate chemotherapy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The systematic salvage surgery combined with an effective chemotherapy demonstrated the survival's improvement. An aggressive approach resulted to be effective in improving survival, which reached 68% and 58% after 3 and 5 years respectively (14).…”
Section: Indicationsmentioning
confidence: 99%